2018
DOI: 10.1140/epje/i2018-11719-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour of colloidal superballs mixed with non-adsorbing polymers

Abstract: Inspired by experimental work on colloidal cuboid-polymer dispersions (Rossi et al., Soft Matter, 7, 4139 (2011)) we have theoretically studied the phase behaviour of such mixtures. To that end, free volume theory (FVT) was applied to predict the phase behaviour of mixtures of superballs and non-adsorbing polymer chains in a common solvent. Closed expressions for the thermodynamic properties of a suspension of hard colloidal superballs have been derived, accounting for fluid (F), face-centred cubic (FCC) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…To assess our proposed mechanism of depletion-driven gelation and better understand the influence of nanocrystal shape on the gelation threshold, we compare theoretical predictions for the phase behavior of the nanocrystal–depletant mixture to our experimental observations. Phase diagrams incorporating depletion attractions for both spherical and cubic nanocrystals are computed using free volume theory and scaled particle theory to determine the spinodal boundaries. Details of these calculations are found in the Supporting Information.…”
mentioning
confidence: 99%
“…To assess our proposed mechanism of depletion-driven gelation and better understand the influence of nanocrystal shape on the gelation threshold, we compare theoretical predictions for the phase behavior of the nanocrystal–depletant mixture to our experimental observations. Phase diagrams incorporating depletion attractions for both spherical and cubic nanocrystals are computed using free volume theory and scaled particle theory to determine the spinodal boundaries. Details of these calculations are found in the Supporting Information.…”
mentioning
confidence: 99%
“…Moreover, it has been shown that anisotropy in the particle shape can be taken into account in a relatively simple manner with FVT. [39][40][41][42] For these reasons, FVT is a promising and versatile method to gain insight into the phase behavior of colloidal mixtures. However, already for the binary hard-sphere mixture, there is a significant discrepancy between the FVT results in comparison with the results from simulations 33 and perturbation theory.…”
Section: Introductionmentioning
confidence: 99%
“…For example, faceted particles have larger overlap volumes than spherical ones, so they experience stronger depletion attractions and assemble at lower c (Figure ). The depletion phase diagram can be computed (nearly) analytically for simple geometries and is quite accurate compared to simulations and experiments with MPs. , Its construction typically involves computing the (semigrand canonical) free energy via thermodynamic integration from a hard-particle reference state with no depletant using well-established results from free volume and scaled particle theories (FVT + SPT). , Because only physical details are needed, this analysis is descriptive of the phase behavior of a broad range of systems.…”
Section: Guiding Principles For Nanocrystal Gelationmentioning
confidence: 99%